The Coiled-Coil NLR Rph1, Confers Leaf Rust Resistance in Barley Cultivar Sudan - Dracatos, Peter Michael; Bartoš, Jan; Elmansour, Huda; Singh, Davinder; Karafiátová, Miroslava; Zhang, Peng; Steuernagel, Burkhard; Svačina, Radim; Cobbin, Joanna C A; Clark, Bethany; Hoxha, Sami; Khatkar, Mehar S; et al. (Plant physiology, 2019)
Unraveling and exploiting mechanisms of disease resistance in cereal crops is currently limited by their large repeat-rich genomes and the lack of genetic recombination or cultivar (cv)-specific sequence information. We cloned the first leaf rust resistance gene Rph1 (Rph1 a) from cultivated barley (Hordeum vulgare) using "MutChromSeq," a recently developed molecular genomics tool for the rapid cloning of genes in plants. Marker-trait association in the CI 9214/Stirling doubled haploid population mapped Rph1 to the short arm of chromosome 2H in a physical region of 1.3 megabases relative to the barley cv Morex reference assembly. A sodium azide mutant population in cv Sudan was generated and 10 mutants were confirmed by progeny-testing. Flow-sorted 2H chromosomes from Sudan (wild type) and six of the mutants were sequenced and compared to identify candidate genes for the Rph1 locus. MutChromSeq identified a single gene candidate encoding a coiled-coil nucleotide binding site Leucine-rich repeat (NLR) receptor protein that was altered in three different mutants. Further Sanger sequencing confirmed all three mutations and identified an additional two independent mutations within the same candidate gene. Phylogenetic analysis determined that Rph1 clustered separately from all previously cloned NLRs from the Triticeae and displayed highest sequence similarity (89%) with a homolog of the Arabidopsis (Arabidopsis thaliana) disease resistance protein 1 protein in Triticum urartu In this study we determined the molecular basis for Rph1-mediated resistance in cultivated barley enabling varietal improvement through diagnostic marker design, gene editing, and gene stacking technologies.
Keywords: interakce hostitele a patogenu; rostlinné proteiny; Chromosome Mapping; Sequence Analysis, DNA; Plant Proteins; ječmen (rod); NLR Proteins; Hordeum; NLR proteiny; rostlinné geny; sekvenční analýza DNA; Host-Pathogen Interactions; Genes, Plant; mapování chromozomů